Histomonosis in Poultry: A Comprehensive Review - Beer, Lesleigh C.; Petrone-Garcia, Victor M.; Graham, B. Danielle; Hargis, Billy M.; Tellez-Isaias, Guillermo; Vuong, Christine N. (Frontiers in Veterinary Science, 2022)
Histomonas meleagridis, etiological agent of histomonosis, is a poultry parasite primarily detrimental to turkeys. Characteristic lesions occur in the liver and cecae, with mortalities in turkey flocks often reaching 80-100%. Chickens and other gallinaceous birds can be susceptible but the disease was primarily considered sub-clinical until recent years. Treating and preventing H. meleagridis infection has become more difficult since 2015, when nitarsone was voluntarily removed from the market, leaving the poultry industry with no approved prophylactics, therapeutics, or vaccines to combat histomonosis. Phytogenic compounds evaluated for chemoprophylaxis of histomonosis have varied results with in vitro and in vivo experiments. Some recent research successes are encouraging for the pursuit of antihistomonal compounds derived from plants. Turkeys and chickens exhibit a level of resistance to re-infection when recovered from H. meleagridis-infection, but no commercial vaccines are yet available, despite experimental successes. Safety and stability of live-attenuated isolates have been demonstrated; furthermore, highly efficacious protection has been conferred in experimental settings with administration of these isolates without harming performance. Taken together, these research advancements are encouraging for vaccine development, but further investigation is necessary to evaluate proper administration age, dose, and route. A summary of the published research is provided in this review.